The apocalyptic vision and the neutering of adventism - Knight, George R. (Review and Herald Publishing Association, 2008)
It is a query that ought to shake you all the way down to the soles of your comfortable shoes. George R. Knight has been wrestling with this very question for nearly five decades. He says he wasn't born that way (like some) and isn't addicted (like others)--hence the struggle. His dilemma?